2012
DOI: 10.1177/1534734612457034
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Demographic Characteristics and the Health-Related Quality of Life in Patients With Diabetic Foot Ulcers at First Presentation

Abstract: To investigate the characteristics of diabetic patients with foot ulcers, their health-related quality of life (HRQoL), and the link between them. The study population included 131 consecutive patients presenting in a diabetic foot clinic with a new foot ulcer between December 1, 2011, and May 1, 2012. The authors collected sociodemographic data, foot and ulcer characteristics using the Wagner Grade, and HRQoL (using the SF-36 Scale) information; 54.2% of the patients were in Wagner 2 or Wagner 3 categories. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…This has a great influence in the development of diabetic foot ulcers because the patients do not fully understand both the importance of taking care of the feet and the severity of having T2DM [20–22]. This is consistent with other studies [2326]. In fact, recent studies have shown that people with a higher level of education are more aware of the severity of having T2DM, take better care of their condition, and participate more in programs devoted to the care of the diabetic foot and the prevention of foot ulcers [27,28].…”
Section: Discussionsupporting
confidence: 88%
“…This has a great influence in the development of diabetic foot ulcers because the patients do not fully understand both the importance of taking care of the feet and the severity of having T2DM [20–22]. This is consistent with other studies [2326]. In fact, recent studies have shown that people with a higher level of education are more aware of the severity of having T2DM, take better care of their condition, and participate more in programs devoted to the care of the diabetic foot and the prevention of foot ulcers [27,28].…”
Section: Discussionsupporting
confidence: 88%
“…42 However, it is usually the combined effect of macrovascular and microvascular complications, comorbid conditions, and background demographic, clinical and treatment satisfaction variables which degrade HRQoL and not diabetes per se. 43 The results of the known-groups comparisons performed here conform to the literature 1,[12][13][14][15]17,[27][28][38][39][40][41] in terms of the score differences and the direction of these differences.…”
Section: Discussionsupporting
confidence: 77%
“…The overall results for the psychometric properties [38][39][40][41] but in the end their absence can be taken as evidence that the instrument is sensitive at its lower end. All SF-36 mean scale scores (not shown) were lower than the respective general population scores reported in the instrument validation study.…”
Section: Discussionmentioning
confidence: 95%
“…The SUV study is certainly one of the most important epidemiological investigations on vascular ulcers of lower limbs carried out in Italy in the recent years, because of the high quantity of data collected (1163 patients, of whom about 50% followed up until 9 months after start of therapy) and the widespread presence of participating centres (59 centres representing 14 Italian regions). Published epidemiological studies have been performed recently in leg ulcers in Romania and New Zealand , in diabetic ulcers in China , in hypertensive leg ulcers in France and in chronic leg wounds in Denmark ; to our knowledge, however, the SUV study is the only one that has involved more than one thousands patients affected by different types of leg ulcers (venous, arterial, diabetic, mixed, etc. ).…”
Section: Discussionmentioning
confidence: 99%